2020
DOI: 10.1111/jgh.15060
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic resection versus transarterial chemoembolization in infiltrative hepatocellular carcinoma: A multicenter study

Abstract: Background and Aim: Prognosis of infiltrative hepatocellular carcinoma (iHCC) is poor, and the treatments selection based on efficacy is unclear. We performed this multicenter study to compare the efficacy of hepatic resection and transarterial chemoembolization (TACE) in treating patients with iHCC. Methods: We retrospectively analyzed the overall survivals (OS) in 319 patients with iHCC who were initially treated by hepatic resection (n = 133) or TACE (n = 186) at four tertiary centers. Fifty-eight patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This finding agreed with previous studies, supporting the advancement of patients with PS1 alone to an advanced stage in the BCLC staging system ( 14 , 25 ). However, some studies have reported contrasting conclusions ( 26 , 27 ). In the HKLC staging system, PS0 and PS1 are equivalent and should be assigned to the same treatments ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding agreed with previous studies, supporting the advancement of patients with PS1 alone to an advanced stage in the BCLC staging system ( 14 , 25 ). However, some studies have reported contrasting conclusions ( 26 , 27 ). In the HKLC staging system, PS0 and PS1 are equivalent and should be assigned to the same treatments ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional treatments include hepatic resection, liver transplantation, local ablation with radiofrequency, and hepatic artery intervention, such as transarterial chemoembolisation etc,. [ 3 , 4 , 5 ]. Currently, systemic therapies including tyrosine kinase inhibitor, immune checkpoint inhibitors,a and monoclonal antibodies have challenged the use of conventional therapies in the treatment of liver cancer [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence and mortality of this malignancy have increased globally and are particularly high in North African and Asian nations (1). Currently, treatments include surgery, transcatheter arterial chemoembolization, liver transplant, radiotherapy, and biotherapy (2,3). Unlike other malignancies, liver cancer is frequently discovered only when it has progressed to the point that liver transplant, surgical treatments, and resection are no longer feasible (4).…”
Section: Introductionmentioning
confidence: 99%